PENGARUH VARIASI DOSIS PUPUK KOMPOS TANAMAN PISANG (Musa paradisiaca L.) TERHADAP PERTUMBUHAN TANAMAN PAKCOY (Brassica rappa L.) SEBAGAI SUMBER BELAJAR BIOLOGI - Patimah, Siti; Asih, Triana; Noor, Rasuane (EDUBIOLOCK, 2020)
The purpose of this study was to determine the effect of variations in the dosage of banana compost fertilizer on the growth of pakcoy plants, to determine the variation in the dosage of compost that gave the best effect and to compile the research results as a source of learning biology. This type of research is an experimental study using RAKL 2 control 4 treatments and 6 replications. The treatments were P1 (0.4 kg/polybag of banana compost), P2 (0.6 kg/polybag of banana compost), P3 (0.8 kg/polybagof banana compost) and P4 (1 kg/polybag compost for banana plants) and control K1 (1/4 kg/polybag cow manure) and K2 (0 kg/polybag fertilizer). Each treatment was given 6 times repetition. The parameters observed were plant height (cm), number of leaves and wet weight (gr) of pakcoy plants. Data were analyzed using One-Way ANOVA (Normality, Homogeneity, Hypothesis and BNJ Test). Based on the results of the study, there was an effect of variations in the dosage of banana compost fertilizer on the growth of pakcoy plants. Hypothesis test results show Fhit> Fdaf. Subsequent testing of BNJ showed that P4 treatment had the best effect on the growth of pakcoy plants. based on the validation analysis of learning resources, this research is suitable of learning biology in the from of brochures.